CAN MOSQUE FUND MANAGEMENT FOR COMMUNITY ECONOMIC EMPOWERMENT? : AN EXPLORATORY STUDY - RB Dandy Raga Utama; Zavirani Fitrandasari; Moh Arifin; Ridan Muhtadi (IJIBE (International Journal of Islamic Business Ethics), 2018)
The actual meaning of the mosque is not limited to a place of prostration but all activities that draw closer to Allah. Mosques as one of the centers for fostering and developing Islamic societies occupy an important role in the process of social change and support the acceleration of development in modern societies, especially in developing spiritual aspects. Mosque prosperity is not only limited to physical development in a state that is beautiful and as grand as possible, but also must be supported by the development of a broader understanding of the function and role of mosques as Islamic social  nstitutions. This  research  is  qualitative  research  by raising the phenomenon of mosques that carry out productive activities  in  order  to  prosper  the  community.  This  study  uses  a phenomenological approach. The object in this study was the Ummul Mu’minin Surabaya mosque. Data collection techniques used observation, interviews and documentation by making takmir and the community as key informants and key informants. The Ummul Mu’minin Mosque is able to maximize the function and role of the mosque optimally. The potential of a mosque that is so great as a place for solving problems in the economic field has been well proven. The mosque funds collected from donors are managed properly and correctly.Keyword: Mosque    Fund    Management,    Economic    Community Empowerment